The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2495/air190061
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ozone Ambient Levels: Case Study of the Fahaheel Urban Area, State of Kuwait

Abstract: Continuously monitored ambient concentrations of ozone (O3), nitrogen monoxide (NO), nitrogen dioxide (NO2), and nitrogen oxides (NOx) for the years 2004-2005 and 2014-2015 are used to understand the relationships and photochemical rections between ozone (O3) and nitrogen oxides (NOX ≈ NO+NO2) in one of Kuwait's major urban areas (Fahaheel). The objective of the study is to investigate the fate of O3 as a secondary pollutant and to determine the chemical coupling and mixing ratio of NO2 to O3. The variation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The Fahaheel area is shown in relation to the Kuwaiti coastline in Figure 1. More details on commuting routes and industrial sites around Fahaheel can be found elsewhere (Al‐Qassimi and Al‐Salem, 2019; Al‐Salem and Khan, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fahaheel area is shown in relation to the Kuwaiti coastline in Figure 1. More details on commuting routes and industrial sites around Fahaheel can be found elsewhere (Al‐Qassimi and Al‐Salem, 2019; Al‐Salem and Khan, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…O X is consequently a more stable entity to study as it shows the potential for renewed production of O 3 (Song et al, 2011). Therefore, work on nitrogen‐based pollutants encompassed the O X filtration procedure for NO and ozone titration established previously by other authors and depicted as follows (Al‐Salem and Khan, 2008, 2010; Pancholi et al, 2018; Tiwari et al, 2015; Al‐Qassimi and Al‐Salem, 2019): OX0.5em[]ppb=O3+NO2 where O X is the total oxidant concentration in the ambient atmosphere (ppb) and values falling below the estimated baseline of O X were discarded due to photo‐oxidation reactions, particulate accumulation, choking or OH ion presence malfunctioning of the instruments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation